2014
DOI: 10.3390/economies2020124
|View full text |Cite
|
Sign up to set email alerts
|

Access to Media and HIV Knowledge in India

Abstract: This paper aims to better understand the relationship between HIV knowledge and media exposure in India. We use a two-stage hurdle model to estimate the effect of media sources such as newspapers, radios and television on AIDS-related knowledge among Indian men and women using demographic health survey data. Overall, access to newspapers, radio, or television increases the likelihood of better HIV knowledge in both males and females by an order between 2% and 12%. These findings, albeit quantitatively small, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
3
7
0
2
Order By: Relevance
“…Similarly, the odds of having comprehensive HIV-knowledge instead of low to moderate among those listening to the radio for less than once a week and at least once a week was higher by 24 and 27% than those not listening at all respectively. This result is concordant with the findings from 27 SSA countries and India where people who frequently watch television and frequently listen to the radio had more comprehensive HIV-knowledge than people who do not [ 34 , 35 ]. Several studies [ 18 , 29 33 ] had also witnessed that exposure to mass media had an impact on acquiring comprehensive HIV-knowledge, due to the HIV-related educations and information conveyed through mass media.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, the odds of having comprehensive HIV-knowledge instead of low to moderate among those listening to the radio for less than once a week and at least once a week was higher by 24 and 27% than those not listening at all respectively. This result is concordant with the findings from 27 SSA countries and India where people who frequently watch television and frequently listen to the radio had more comprehensive HIV-knowledge than people who do not [ 34 , 35 ]. Several studies [ 18 , 29 33 ] had also witnessed that exposure to mass media had an impact on acquiring comprehensive HIV-knowledge, due to the HIV-related educations and information conveyed through mass media.…”
Section: Discussionsupporting
confidence: 89%
“…This could be due to differences in access to mass media between urban and rural youths which play a very vital role in disseminating HIV-related educations and awareness creations. This study and other studies [18,[29][30][31][32][33][34][35][36][37][38][39] depicted that exposure to mass media is associated with acquiring comprehensive HIVknowledge.…”
Section: Discussionsupporting
confidence: 66%
“…Ethiopian youths who listen to the radio at least once a week were 1.33 times more likely to accept HIV voluntary counseling and testing compared to their Ethiopian peers who did not listen to the radio. The findings from secondary data analysis of DHSs data from 27 SSA countries and DHS data from India showed that people who frequently watch television and frequently listen to the radio had more comprehensive HIV knowledge than people who do not [ 45 , 47 ]. Many other studies [ 29 , 44 , 46 , 48 , 49 , 51 ] had also witnessed that exposure to mass media has an independent impact on acquiring comprehensive HIV knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…En cambio, se reporta mejor nivel de actitudes adecuadas en personas que no trabajan (15) , y tener trabajo se asocia con conducta sexual de riesgo (28) lo que es contrario a nuestros hallazgos. Tener mayor acceso a medios de comunicación se asoció en la literatura con mejor nivel de conocimiento (12,14) , menores niveles de actitudes estigmatizantes hacia las PVVS (17) y con mayor uso de condón (14) , de manera similar a nuestro estudio.…”
Section: Discussionunclassified
“…La información existente en la literatura indica que un mayor nivel educativo (8)(9)(10)(11)(12) , mejor nivel socioeconómico (8,9,12,13) , mayor acceso a los medios de comunicación (12,14,17) y el tener empleo (15,16) están asociados con un mejor conocimiento sobre VIH/ SIDA y en menor grado con el uso consistente de condón por parte de la pareja (12,14) .…”
Section: Artículo Originalunclassified